Extending Semantic Provenance into the Web of Data - Zhao, J; Sahoo, S; Missier, P; Sheth, A; Goble, C (2011)
In this article, the authors provide an example workflowand a simple classification of user questions on the workflow's data productsto combine and interchange contextual metadata through a semantic data model and infrastructure. They also analyze their approach's potential to support enhanced semantic provenance applications. © 2011 IEEE.